Adhesion to treatment and related pathologies in insulin dependent patients in the municipality of Corbélia – Paraná (Research, Society and Development, 2021)
Introduction: the diabetic patient often does not adhere to insulin treatment, even with all the adversities that the pathology may provide. Objective: to carry out a survey in a basic pharmacy in western Paraná, with the aim of analyzing patients' adherence to insulin treatment and possible concomitant pathologies that they may present. Methodology: interviews were carried out through a semi-structured questionnaire where the participants were patients who carried out the withdrawal of supplies at the pharmacy. Results: 50 patients were interviewed where they were 25 men (50%) and 25 women (50%), with a mean age of 64 years, the most present body mass index (BMI) was overweight (32%), the pathologies more present in both groups were hypertension (84%) men and (88%) women and dyslipidemia (64%) for both, the most used drugs in the male group were Simvastatin (56%), Losartan (36%) and for women , Losartan (56%) and Simvastatin (48%). Conclusion: The most common pathologies were hypertension and dyslipidemia, but there was no great divergence between the groups, the most preferable treatment was with Losartan and Simvastatin.